Do rhomboid flaps provide more elongation than Z-plasty flaps? An experimental study. Issue 3 (4th May 2018) - Altun, Serdar; Çakır, Fatih; Öztan, Mehmet; Okur, Mehmet İhsan and Bal, Ali
Abstract: Background and aim: A Z-plasty flap is one of the most widely used geometric relaxation methods to release contracture bands. A rhomboid flap is a lesser used geometric relaxation method than a Z-plasty flap. This study aimed to determine the length and rate of elongation provided by rhomboid and Z-plasty flaps. Methods: Bilateral contracture bands were created in the inguinal skins of rats. A rhomboid flap was planned for the right side of the inguinal region, and a single Z-plasty flap was planned for the left side. The length and rate of elongation provided by the two flaps were calculated after completing the procedures and were compared using Student's t -test. Results: Experimental contracture bands disappeared in both the inguinal regions after creating rhomboid and Z-plasty flaps. The mean postoperative elongation of the contracture band was 1.4 ± 0.119 and 2.47 ± 0.281 cm using the rhomboid and Z-plasty flaps, respectively. The difference was statistically significant ( p < .001). Conclusion: Z-plasty flaps provide more elongation than rhomboid flaps and also appear to be better options for releasing linear contracture bands. However, rhomboid flaps may be used as alternatives when Z-plasty flaps cannot be used and in regions such as the axilla, genital region, nipple-areola, where their distortion effects should be avoided.